Mathematical Modeling of Hepatitis Transmission Using the SEIR Model and Batik-Inspired Motifs from Simulation - Rahmadina, Alifah Fitria; Hanifah, Jeisinta Hana; Sabila, Robit Ma’rufi; Sugiyanto, Sugiyanto (Proceeding International Conference on Religion, Science and Education, 2026)
Hepatitis is an infectious disease that remains a major health problem in Indonesia. This study aims to model the spread of hepatitis using the SEIR (Susceptible, Exposed, Infected, Recovered) mathematical model and connect it with the concept of batik patterns as a medium of mathematical visualization. The research employs a literature study and numerical simulation based on secondary data of hepatitis patients from Dr. M. Haulussy Ambon Hospital in 2019. The SEIR model describes the dynamic transitions among subpopulations of susceptible (S), exposed (E), infected (I), and recovered (R) individuals. The concept of batik patterns is used to represent the regularity and interconnectedness among the model’s compartments, where each motif symbolizes dynamic and repetitive population interactions—analogous to the rhythm of disease transmission. The analysis results reveal two equilibrium points: the endemic equilibrium and the disease-free equilibrium, with the system being stable according to the Routh–Hurwitz criteria. Integrating mathematical modeling with the philosophy of batik offers an interdisciplinary approach that is both analytical and aesthetic. This study hightlights that the that the harmony between science and culture can enrich the way infectious disease phenomena are understood within society.